2012
DOI: 10.1007/978-3-642-33454-2_68
|View full text |Cite
|
Sign up to set email alerts
|

Automated Colorectal Cancer Diagnosis for Whole-Slice Histopathology

Abstract: Abstract. In this study, we propose a computational diagnosis system for detecting the colorectal cancer from histopathological slices.The computational analysis was usually performed on patch level where only a small part of the slice is covered. However, slice-based classification is more realistic for histopathological diagnosis. The developed method combines both textural and structural features from patch images and proposes a two level classification scheme. In the first level, the patches in slices are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…An early study by Esgiar et al already showed that entropy texture features extracted from GLCM was capable of differentiating between normal and neoplastic tissue [27]. Additionally, by performing color channel histograms, GLCM, and structural features, Kalkan et al achieved an accuracy of 75.15% in the classification of four types of colon tissues: normal, cancerous, adenomatous, and inflammatory [28]. In our study, a higher GLCM Contrast and a lower GLCM Correlation are also in line with the recent results by Chaddad et al, who report the use of TA extracted from multispectral optical microscopy images for the classification of three types of pathological tissues: benign hyperplasia, intraepithelial neoplasia, and carcinoma [29].…”
Section: Discussionmentioning
confidence: 99%
“…An early study by Esgiar et al already showed that entropy texture features extracted from GLCM was capable of differentiating between normal and neoplastic tissue [27]. Additionally, by performing color channel histograms, GLCM, and structural features, Kalkan et al achieved an accuracy of 75.15% in the classification of four types of colon tissues: normal, cancerous, adenomatous, and inflammatory [28]. In our study, a higher GLCM Contrast and a lower GLCM Correlation are also in line with the recent results by Chaddad et al, who report the use of TA extracted from multispectral optical microscopy images for the classification of three types of pathological tissues: benign hyperplasia, intraepithelial neoplasia, and carcinoma [29].…”
Section: Discussionmentioning
confidence: 99%
“…Manually designed features include fractal features [ 29 ], morphometric features [ 30 ], textural features [ 31 ], and object-like features [ 32 ]. Kalkan [ 33 , 34 ] exploits textural and structural features from patch-level images and proposes a two-level classification scheme to distinguish between cancer and non-cancer in colon cancer. Chang [ 35 ] proposes sparse tissue morphometric features at various locations and scales to distinguish tumor, necrosis, and transition to necrosis for the GBM dataset and tumor, normal, and stromal for the KRIC dataset.…”
Section: Introductionmentioning
confidence: 99%
“…The classifier exploits image-level information and alteration in cell formations under different cancer states. Kalkan [ 33 ] proposes a two-stage classification. The first stage classifies patches into possible categories (adenomatous, inflamed, cancer and normal).…”
Section: Introductionmentioning
confidence: 99%
“…While the proposed taxonomy allows for heterogeneity in training and test objects (i.e., SI-MI and MI-SI), it is limited because the training or test objects themselves are homogeneous. It would be interesting to investigate what happens in the case where in the training phase both labeled bags and labeled instances are available, such as in [22]. As we already discussed in Section 3.4, the optimal bag classifier does not necessarily correspond with the optimal instance classifier.…”
Section: Discussionmentioning
confidence: 99%